2014
DOI: 10.1136/emermed-2012-202016
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for attending an urban urgent care centre with minor illness: a questionnaire study

Abstract: We found that the GP-led urgent care centre was similar to walk in centres in attracting healthy young adults, who were mostly registered with a GP and used services because of convenience and ease of access rather than satisfaction levels with their GP. This group may benefit from being seen as part of routine general practice care to provide opportunities for education and promotion of self-management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 15 publications
(13 reference statements)
3
37
0
Order By: Relevance
“…Another factor was lack of awareness of other services, with one study reporting that seven of 30 patients who attended ED had no knowledge of alternative primary care options 38. GP dissatisfaction influenced 10% of patients in their decision to attend an urgent care center39 and in some cases high rates of PCP dissatisfaction was reported 45. One study reported that patients felt that out‐of‐hours care was impersonal 46…”
Section: Resultsmentioning
confidence: 99%
“…Another factor was lack of awareness of other services, with one study reporting that seven of 30 patients who attended ED had no knowledge of alternative primary care options 38. GP dissatisfaction influenced 10% of patients in their decision to attend an urgent care center39 and in some cases high rates of PCP dissatisfaction was reported 45. One study reported that patients felt that out‐of‐hours care was impersonal 46…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a survey of 1886 patients attending 20 walk-in centres throughout England, 22% of responders registered to a general practice elsewhere had tried but were unable to obtain a convenient general practice appointment 16. At an urgent care centre co-located with an emergency department in London, England, 20% of surveyed patients attending with ‘minor illness’ had been unable to obtain a timely general practice appointment;17 58% of patients had stated that one reason for their attendance was that it was ‘quicker than getting a GP appointment’,17 and the large majority of all attendees could have been managed by a GP or emergency nurse practitioner 18. A GP panel review of a random sample of 629 clinical case notes from patients attending an emergency department in Oxford, England, concluded that approximately 43% of patients could have been managed by a GP 19.…”
Section: Discussionmentioning
confidence: 99%
“…The number of EDs visit is on the increase, and the pressure on EDs is of significant concern worldwide 1. The usage of EDs by patients with minor illness is an important and still unresolved problem, which places significant burden on healthcare services,2 increases waiting times in the ED3 and is of significant concern to ED staff, ED directors and policy makers 4…”
Section: Introductionmentioning
confidence: 99%